Методы инструментальной обработки корневых каналов зубов (Эндодонтия Today)
The article describes the various methodics of instrumental processing of root canals of teeth. Among them there are two basic ones - Step Back and Crown Down. In laboratory and clinical studies the authors developed the methodology of combined use of files from different systems for the preparation of a root canal according to its morphological features, which allows a full treatment of that canal throughout all its area and length.